2018
DOI: 10.1002/wea.3085
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between meteorological factors and the risk of bacillary dysentery in Hunan Province, China

Abstract: Meteorological factors are known to influence the morbidity of bacillary dysentery in humans in a number of different regions. To investigate the effect of meteorological factors on the incidence of this disease in the Hunan Province of China, Xiangxi, the region with the highest annual average incidence of bacillary dysentery in the Hunan province from 2005 to 2010 (44.07 cases per 100 000 people) was selected as the area of study, based on spatial descriptive analysis. Spearman correlation analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…About the positive correlation between them, this is congruous with the recent findings from the studies in Jinan 14,26 and Auckland 67 , which found that temperature was positively associated with pertussis among different age groups and could be considered as a good predictor. Also, in line with the findings that have been observed in other infectious diseases, such as HFMD (in Guangdong) 68 , bacillary dysentery (in Hunan Province) 31 , and scarlet fever (in Hefei City) 69 . Prior work discovered that extreme heat was positively linked to respiratory diseases 70 , and the patients visiting respiratory emergency department significantly increased during hot weather 71 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…About the positive correlation between them, this is congruous with the recent findings from the studies in Jinan 14,26 and Auckland 67 , which found that temperature was positively associated with pertussis among different age groups and could be considered as a good predictor. Also, in line with the findings that have been observed in other infectious diseases, such as HFMD (in Guangdong) 68 , bacillary dysentery (in Hunan Province) 31 , and scarlet fever (in Hefei City) 69 . Prior work discovered that extreme heat was positively linked to respiratory diseases 70 , and the patients visiting respiratory emergency department significantly increased during hot weather 71 .…”
Section: Discussionsupporting
confidence: 89%
“…As for such a discrepancy, this is largely due to the fact that temperature and rainfall were only included in that study 14 . Currently, many water-borne pathogens and vector-borne infectious diseases have been found to be positively linked to precipitation, such as dengue fever 19 , bacillary dysentery 31 , HFRS 72 , etc., which because rainfall can mainly impact such diseases via affecting the development of pathogens and the vectors/hosts 74 . However, there is a current scarcity of relative study and biological evidence to clarify the relationship between rainfall and respiratory diseases, albeit several studies exhibited that precipitation may be associated with scarlet fever 17 , 75 and mumps 57 , their findings are contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al ( 2019 ) used the Poisson model to explore the association between total cases and meteorological variables. Poisson regression is a commonly used classical model, which was based upon the classical assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the GAM was applied to establish a dose-response function, which connected different dose variables (outbreak days, average temperature, rainfall, and humidity), with a probability of COVID-19 infection (response variable). Li et al (2019) used the Poisson model to explore the association between total cases and meteorological variables. Poisson regression is a commonly used classical model, which was based upon the classical assumptions.…”
Section: Correlation Analysismentioning
confidence: 99%